Metode Pendidikan Akhlak Islam dalam Keluarga Terhadap Remaja di Dusun Ranjingan Klapagading Kulon Wangon Banyumas - Rindi Agustiana; Mintaraga Eman Surya (UM Purwokerto Press, 2023)
The character of adolescents who are emotional and do not have stability in choosing a way out has a high potential to direct adolescents to negative values or what is often known as juvenile delinquency, especially in the village of Ranjingan. Therefore, Islamic moral education from parents is important as a guide and provision for teenagers. in overcoming uncontrollable desires and emotions. The purpose of this study was to find out various methods of Islamic moral education in families in the village of Ranjingan for adolescents. This research is field research with data collection techniques reservation interviews, and documentation. Analysis of data related to the method of Islamic moral education in the family was analyzed qualitatively using the description method where data obtained from interviews, observations, and documentation will be described in option a general conclusion. This study resulted in the method of Islamic moral education used by parents in Ranjingan hamlet, namely the exemplary method, the advice method, the punishment method, and the habituation method as well as various other supporting methods that are not dominant in this Islamic moral education. The parents said that the Islamic moral education given to their teenagers was dominated by freedom of choice, and opinion determining mine the actions taken by teenagers when they behaved at home and in society, however, parents still provide supervision, although not with such involvement. dominant in the daily activities of the youth in the village of Ranjingan.